2015
DOI: 10.1007/s13277-015-4011-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor M3 mediates cell proliferation induced by acetylcholine and contributes to apoptosis in gastric cancer

Abstract: The muscarinic receptor M3 is an acetylcholine receptor that regulates the activity of numerous fundamental central and peripheral nervous system functions. Recent studies have identified the activation of the M3 receptor in several cancers; however, the role of M3 in human gastric cancer (GC) remains largely unknown. In this study, we demonstrated that the M3 receptor was overexpressed in human GC tissues and was correlated with the cancer stage and with lymph node metastasis. In vitro, the M3 receptor enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Recent years, increasing evidences demonstrated that M3R may play a vital role in the carcinogenesis of many types of cancer, including colon cancer, lung cancer, and cholangiocarcinoma323334. Notably, in human gastric cancer tissue, M3R was over-expressed and correlated with the cancer stage and lymph node metastasis19. Those studies, combined with our preliminary data suggested that M3R plays a major role in ACh stimulated gastric cell proliferation.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Recent years, increasing evidences demonstrated that M3R may play a vital role in the carcinogenesis of many types of cancer, including colon cancer, lung cancer, and cholangiocarcinoma323334. Notably, in human gastric cancer tissue, M3R was over-expressed and correlated with the cancer stage and lymph node metastasis19. Those studies, combined with our preliminary data suggested that M3R plays a major role in ACh stimulated gastric cell proliferation.…”
Section: Discussionsupporting
confidence: 65%
“…9a). Our data was also consistent with Wang et al .’s study which indicated the proliferation-promoting role of ACh in gastric cancer cells19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggested that M3 in PDAC could play a significant role in the invasive process in vivo. Recent investigations into the functional role of M3 in carcinomas have demonstrated that the expression of M3 augmented cell motility on extracellular matrix components47 and promoted tumor growth in mice16,17 in addition to its effect on cancer cell proliferation 18. These findings support our hypothesis that M3 in PDAC could play a role in the invasive process and its expression could be a more malignant phenotype.…”
Section: Discussionsupporting
confidence: 88%
“…The immunohistochemistry method was performed as described preciously [28]. Smad3 (diluted 1:250, Abcam) was used as primary antibodies.…”
Section: Methodsmentioning
confidence: 99%